2013
DOI: 10.7314/apjcp.2013.14.5.3093
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of β-catenin and Cyclooxygenase-2 Expression and Cell Proliferation in Azoxymethane-Induced Colonic Cancer in Rats by Rice Bran Phytic Acid (PA)

Abstract: Background: Phytic acid (PA) is a polyphosphorylated carbohydrate that can be found in high amounts in most cereals, legumes, nut oil, seeds and soy beans. It has been suggested to play a significant role in inhibition of colorectal cancer. This study was conducted to investigate expression changes of β-catenin and cyclooxygenase-2 (COX-2) and cell proliferation in the adenoma-carcinoma sequence after treatment with rice bran PA by immunocytochemistry. Materials and Methods: Seventy-two male Sprague-Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
(43 reference statements)
3
24
0
Order By: Relevance
“…And the last, data were not stratified by other factors such as age, gender, family history, lifestyle variables, because insufficient information could be extracted from the primary publication. It is worth mentioning a study published by Saad et al (Saad et al, 2013), the study indicated potential value of PA extracted from rice bran in reducing colonic cancer risk in rats. Which may have implications for further medical research concerning digestive system cancer and personalized therapy for digestive system cancer patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…And the last, data were not stratified by other factors such as age, gender, family history, lifestyle variables, because insufficient information could be extracted from the primary publication. It is worth mentioning a study published by Saad et al (Saad et al, 2013), the study indicated potential value of PA extracted from rice bran in reducing colonic cancer risk in rats. Which may have implications for further medical research concerning digestive system cancer and personalized therapy for digestive system cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence suggests that COX-2 plays an key role in the carcinogenesis pathway, such as in the inhibition of apoptosis, tumor growth, angiogenesis, invasion and metastasis (Leahy et al, 2000;Tatsuguchi et al, 2004;Wang et al, 2007;Gu et al, 2012;Huang et al, 2013;Saad et al, 2013), which are all crucial to many cancers, especially those belonging to the gastrointestinal tract, such as oral cancer (Chiang et al, 2008), gastric cancer (Liu et al, 2006), esophageal cancer (Kristinsson et al, 2009;Upadhyay et al, 2009), and colorectal cancer (Cox et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The complex plays important roles in maintaining integrity of cellular structure (Yagi et al, 2000;Ivanov et al, 2001). Reduced expression of one or more components of this complex in tumor cells could destroy the junctional structure, result in loss of intercellular adhesion and consequently facilitate tumor differentiation and metastasis (Saad et al, 2013;Yu et al, 2014). It has been reported that reduced membranous β-catenin expression was related to poor survival and prognosis in a portion of cancers (Krishnadath et al, 1997;Wang et al, 2011;Guan et al, 2012;Mei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingadiene is a derivative of sphigolipid inhibits colon cancer by downregulating wnt/β-catenin pathway (Kumar et al, 2013). Phytic acid is a product of rice bran known to inhibit β-catenin during AOM-induced colon cancer (Saad et al, 2013;Shafie et al, 2013). Berberine acts as a natural inhibitor of Wnt/β-catenin signaling in HCT-116 colon carcinoma cells (Albring et al, 2013).…”
Section: Wnt/β-catenin Signaling and Colon Cancermentioning
confidence: 99%